PENGARUH ELECTRONIC WORD OF MOUTH (EWOM), KUALITAS PRODUK, HARGA, CITRA MEREK DAN PROMOSI TERHADAP MINAT BELI PADA PRODUK NU SKIN SKINCARE DI KOTA YOGYAKARTA - Hardoko, Hardoko; Abdul Hadi Hari,; Christina Dini Ika Handayani,; Febri Dhol Khori, (Juremi: Jurnal Riset Ekonomi, 2025)
This study aims to determine: (1). The effect of electronic word of mouth (eWOM) on buying interest in Nu Skin Skincare products, (2). The effect of product quality on buying interest in Nu Skin Skincare products, (3). The effect of price on buying interest in Nu Skin Skincare products, (4). The effect of brand image on buying interest in Nu Skin Skincare products, (5). The effect of promotion on buying interest in Nu Skin Skincare products, (6) The effect of electronic word of mouth (eWOM), product quality, price, brand image and promotion on buying interest in Nu Skin Skincare products.This study used a purposive sampling method with a sample size of 100 people. The measurement scale uses a Likert scale. For data processing using SPSS version 13. The results of the study obtained the regression equation as follows: Y = -1.703 + 0.020X1 + 0.369X2 + 0.208X3 + 0.559X4 + e. Hypothesis testing using the t test shows that partially the electronic word of mouth (eWOM) variable (X1), price (X3), brand image (X4)) have no significant effect on purchase intention, while product quality (X2) and promotion (X5) have a positive and significant effect on purchase intention. Then through the F test it is known that the variables electronic word of mouth (eWOM) (X1), product quality (X2), price (X3), and promotion (X4) simultaneously have a positive and significant effect on purchase intention (Y)